Development of Linguistic Approach to the Problem of the Computer Electro-cardiogram's Classifications - Fainzilberg, L.S.; Dykach, Ju.R. (Control systems & computers, 2021)
Six decision rules based on the analysis of the Levenshtein distances and the number of occurrences of characteristic patterns of codewords are considered and investigated. It has been shown that using of the developed decision rules makes it possible to increase the sensitivity and specificity of diagnos-tics even in cases when the ECG does not show traditional electrocardiological signs of myocardial ischemia..